2007
DOI: 10.1172/jci30954
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the key enzyme of sialic acid biosynthesis causes severe glomerular proteinuria and is rescued by N-acetylmannosamine

Abstract: Mutations in the key enzyme of sialic acid biosynthesis, uridine diphospho-N-acetylglucosamine 2-epimerase/N-acetylmannosamine (ManNAc) kinase (GNE/MNK), result in hereditary inclusion body myopathy (HIBM), an adult-onset, progressive neuromuscular disorder. We created knockin mice harboring the M712T Gne/Mnk mutation. Homozygous mutant (Gne M712T/M712T ) mice did not survive beyond P3. At P2, significantly decreased Gne-epimerase activity was observed in Gne M712T/M712T muscle, but no myopathic features were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
187
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(205 citation statements)
references
References 58 publications
12
187
3
3
Order By: Relevance
“…This selective phenotypic manifestation clearly differentiates the new mouse model from the earlier described Gne M712T/M712T mouse, 21 in which podocytopathy developed on the background of a constitutively and systemically depressed sialylation (see the defective NCAM polysialylation in Gne M712T/M712T mouse brain). Moreover, Gne M712T/M712T mice are smaller than wt littermates at the day of birth, showing petechial hemorrhages and split GBMs.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This selective phenotypic manifestation clearly differentiates the new mouse model from the earlier described Gne M712T/M712T mouse, 21 in which podocytopathy developed on the background of a constitutively and systemically depressed sialylation (see the defective NCAM polysialylation in Gne M712T/M712T mouse brain). Moreover, Gne M712T/M712T mice are smaller than wt littermates at the day of birth, showing petechial hemorrhages and split GBMs.…”
Section: Discussionmentioning
confidence: 58%
“…21 Not surprising thus that animal models exhibiting mutations that lead to a general decrease in cellular Sia levels develop nephropathies. 21,30,31 The nls/nls mouse model, however, is the first that unequivocally identified the candidates and processes that crucially depend on sialylation during the construction of the size and charge controlled filtration barrier. Although CMAS mutations in humans presumably result in embryonic lethality and may not be of postnatal clinical relevance, the pathology of acquired sialylation deficiencies caused by neuraminidase producing germs may include targets as described for nls/nls mice.…”
Section: Discussionmentioning
confidence: 99%
“…In certain muscle glycoproteins, including ␣-dystroglycan, increased reactivity to peanut agglutinin, a lectin that is reactive to desialylated forms of O-glycans, was observed (30); thus, it was proposed that the stability of such glycoproteins could be influenced by sialylation, and therefore these proteins could be involved in the pathomechanism of DMRV/hIBM. Likewise, it was also hypothesized that hyposialylation of neural cell adhesion molecule and NEP (26,32) may contribute to the symptomatology of disease. In this study, we showed that hyposialylation of transferrin in blood, ␣SG and NEP in skeletal muscle, and podocalyxin in both kidney and skeletal muscles of DMRV/hIBM mouse were almost completely recovered after Ac 4 ManNAc treatment, although until now, the relevance of changes in specific glycoproteins was still being clarified.…”
Section: Discussionmentioning
confidence: 99%
“…) (32). In the kidney and skeletal muscle of DMRV/hIBM mice, podocalyxin from DMRV/hIBM placebo mice was indeed hyposialylated, migrating more slowly than littermate control (supplemental Fig.…”
Section: M712t/m712tmentioning
confidence: 93%
“…At least some of PC's molecular functions in normal and neoplastic tissues can be explained by viewing PC as a key electrostatic anti-adhesive force between extracellular membrane surfaces (Gelberg et al, 1996;Takeda et al, 2000;Galeano et al, 2007;Strilic et al, 2009). However, since the intracellular domain of PC is phosphorylated on Ser/Thr and Tyr residues and PC assembles signalling complexes in response to cell activation, PC undoubtedly influences the behaviour of tumour cells by regulating intracellular signalling pathways.…”
Section: The Molecular Basis For Podocalyxin Function In Tumour Metasmentioning
confidence: 99%